2007
DOI: 10.1161/01.hyp.0000250088.15021.c2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Activation of Dorsal Hindbrain Corticosteroid Receptors Augments the Arterial Pressure Response to Acute Stress

Abstract: Abstract-Augmented cardiovascular responses to acute stress can predict cardiovascular disease in humans. Chronic systemic increases in glucocorticoids produce enhanced cardiovascular responses to psychological stress; however, the site of action is unknown. Recent evidence indicates that glucocorticoids can act within the dorsal hindbrain to modulate cardiovascular function. Therefore, we tested the hypothesis that the endogenous glucocorticoid corticosterone can act in the dorsal hindbrain to enhance cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
1
21
1
Order By: Relevance
“…In adult rats, chronic increases in dorsal hindbrain corticosterone have been reported to produce an enhanced pressor response to restraint (35). However, in the present study, there was no difference in either basal or stressed corticosterone levels in NS vs. HS female offspring.…”
Section: Discussioncontrasting
confidence: 87%
“…In adult rats, chronic increases in dorsal hindbrain corticosterone have been reported to produce an enhanced pressor response to restraint (35). However, in the present study, there was no difference in either basal or stressed corticosterone levels in NS vs. HS female offspring.…”
Section: Discussioncontrasting
confidence: 87%
“…We previously demonstrated that chronic treatment of the DHB with exogenous corticosterone increased the arterial pressure and glucose responses to acute restraint stress in normotensive rats (56). The present study demonstrates that blockade of DHB GR with Mif attenuates the arterial pressure response to acute restraint stress in BHR, but has no affect on this response in WKY rats.…”
Section: Effects Of Rat Strain and Endogenous Corticosterone On Resposupporting
confidence: 50%
“…Other studies indicate that chronic, systemic elevations in glucocorticoids enhance cardiovascular and catecholamine responses to acute novel psychological stress (33,64). We demonstrated that chronic administration of the glucocorticoid corticosterone to the dorsal hindbrain (DHB) enhances the blood pressure and glucose responses to acute novel stress, without altering the systemic corticosterone or heart rate responses (56). Thus, exogenously administered glucocorticoids can act within the brain to modulate the cardiovascular response to psychological stress.…”
mentioning
confidence: 99%
“…To this point, it has been indicated that chronic stress does not have an effect on BP (Scheuer et al 2007;Bechtold et al 2009;Scheuer 2010) and nesfatin-1 increases BP Samson 2009, 2010;García-Galiano et al 2010). Yosten and his colleagues have showed that intracerebroventricular nesfatin-1 administration increases BP (Yosten and Samson 2009) and this effect of nesfatin-1 occurs via sympathetic system activation (Yosten and Samson 2010).…”
Section: Discussionmentioning
confidence: 99%